Evaluate -y+(-z)+7.99−y+(−z)+7.99minus, y, plus, left parenthesis, minus, z, right parenthesis, plus, 7, point, 99 where y = 1.46y=1.46y, equals, 1, point, 46 and z = 3.82z=3.82z, equals, 3, point, 82.

Respuesta :

The solution is [tex]2.71[/tex]

Explanation:

The expression is [tex]-y+(-z)+7.99[/tex]

where [tex]y=1.46[/tex] and [tex]z=3.82[/tex]

To determine the value of the expression, let us substitute the value of y and z in the expression.

Thus, the expression becomes,

[tex]-1.46+(-3.82)+7.99[/tex]

Simplifying, we have,

[tex]-1.46-3.82+7.99[/tex]

Adding the negative terms, we get,

[tex]-5.28+7.99[/tex]

Adding, we have,

[tex]2.71[/tex]

Thus, the solution is [tex]2.71[/tex]

Answer:

2.71

Step-by-step explanation: